Cilvēkkapitāla vērtības paaugstināšana izglītības nozarē strādājošiem - Stulberga, Kristīne (Latvijas Universitāte, 2019)
Kristīne Stulberga. Maģistra darbs. Cilvēkkapitāla vērtības paaugstināšana izglītības nozarē strādājošiem – Rīga: Latvijas Universitāte, 2019.- 77 lpp. Maģistra darba mērķis ir analizēt literatūras avotus, par cilvēkkapitāla attīstību, problēmām un perspektīvām, kā arī veikt empīrisku pētījumu par cilvēkkapitāla paaugstināšanas veidiem izglītības nozarē. Autore veica literatūras avotu izpēti par cilvēkkapitāla jēdzienu, cilvēkresursiem, iestāžu vadību, mūžizglītību, pedagoģiskās darbības, izglītības sistēmas pārmaiņām. Empīriskā pētījuma metodes bija anketēšana un intervēšana. Datu analīze parādīja, ka pedagoģiskie darbinieki ir motivēti pilnveidoties un vēlas aktīvāku iestāžu vadītāju atbalstu ieguldījumam cilvēkkapitāla vērtību paaugstināšanai izglītības nozarē.

Kristīne Stulberga. Master’s Thesis. Improvement of the Value of Human Capital for the Employees of the Education Sector – Riga: University of Latvia, 2019 – 77 pages. Purpose of the Master’s Thesis is – to analyse literature sources regarding the development, problems and prospects of human capital, as well as to conduct an empirical research on ways of improvement of the human capital in the education sector. Author of the thesis conducted research of literature sources regarding the concept of human capital, human resources, management of institutions, lifelong education and changes in the pedagogical activities and educational system. Methods of the empirical research were: surveys and interviews. Data analysis showed that employees of the education sector are motivated for improvements and wish more active support of the managers of the educational institutions for the improvement of the values of human capital in the education sector. Keywords – Human Capital, Lifelong education, Management, Education
Increasing the value of human capital in the education sector
Keywords: Izglītības vadība; Cilvēkkapitāls; Mūžizglītība; Vadība; Izglītība